Pengaruh Pemberian Insentif Terhadap Disiplin Kerja Guru Karyawan di SMP Muhammadiyah Al Mujahidin - Fidyah Hety Apsari; Yustika, Gaung Perwira (Ebisma (Economics, Business, Management, & Accounting Journal), 2025)
SMP Muhammadiyah Al Mujahidin is a leading school in Gunungkidul Regency which has 60 teachers and 52 employees. In terms of payroll systems tend to differ between statuses. There are three groups or levels in employee status including Teachers/Contract employees, Teachers/Temporary Employees of the Foundation, Teachers/Permanent Employees of the Foundation. The three levels of status clearly affect the receipt of their respective salaries. In addition to class, incentives also greatly affect the amount of salary received by each teacher/employee. The research subjects were some teachers and employees at SMP Muhammadiyah Al Mujahidin with details of 34 teachers and 23 employees. The data taken is data on receiving teacher and employee incentives in September 2022 using the sampling method through interviews with selected teachers and employees and the school treasurer, still with the permission of the school principal. The results showed that of the 57 samples through statistical tests with SPSS software, there is a relationship between intensive giving and work discipline with a correlation of 0.651 (correlation is significant at the 0.01 level (2-tailed).